Corporate Criminal Liability Formulation in Criminal Acts in the Field of Taxation to Realize Legal Certainty - Basuki Rekso Wibowo; Hendrik Handoyo Lugito; Lilik Mulyadi (Pelopor Publikasi Akademika, 2024)
Problems in the enforcement of tax criminal law involve normative vagueness related to corporate criminal liability in the context of tax crimes. Currently, criminal liability is directed only to individuals who are stewards or controllers of the corporation personally. This results in the main perpetrator in tax crimes are individual taxpayers, even though these crimes actually occur within the scope of operations of a corporation. In addition, the corporation itself cannot be criminally liable, nor can its shareholders. In the context of tax crimes that generally occur in a corporative environment and involve tax officials, there are normative obstacles in law enforcement against business entities involved in tax crimes. The research method used in this study is normative juridical with research specifications, namely descriptive analytical, techniques for collecting legal materials with library research using primary, secondary and tertiary legal materials, analytical techniques used qualitative normative by combining induction and deduction reasoning. The results of this Dissertation research show that criminal liability for corporations in tax crimes regulated in Law No. 16 of 2009 concerning General Provisions and Tax Procedures which has been amended by Law No. 7 of 2021 concerning Harmonization of Tax Regulations, has not directly regulated criminal liability for corporations. Currently, criminal liability is only given to the management or controller of the corporation personally.